Urinary Tract Infections in Pediatric Oncology Patients with Fever and Neutropenia (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Background: The relevancy of the urinary tract as a source of infection during febrile neutropenia is still to be known. We sought to determine the frequency of urinary tract infections (UTIs) in pediatric cancer patients with febrile neutropenia.Methods: Urine was collected from a mid-stream void before the administration of antibiotics. Demographic, clinical, and laboratory data were collected. The frequency of UTI and usefulness of urinalysis and localizing signs in predicting UTI in pediatric cancer patients with fever and neutropenia were determined.Results: Forty-five patients who had 58 febrile neutropenic episodes were included in the study for participation. No patient presented with localizing signs. The urinalysis was negative in 53 episodes and positive in 5 episodes. Four patients had 5 UTIs. The frequency of UTI was 8.6% (5 of 58 febrile neutropenia episodes). Four patients had bacteremia, none of whom had a UTI. The sensitivity, specificity, and negative predictive value of urinalysis was 40%, 94%, and 94%, respectively, and for localizing signs was undefined, 100%, and 91%, respectively.Conclusions: UTI is as common as bacteremia in the current pediatric cancer patients with fever and neutropenia. Urinalysis and urine culture should be obtained routinely as part of the diagnostic evaluation of patients with fever and neutropenia.DOI: http://dx.doi.org/10.11566/cmoshmcj.v12i2.34Chatt Maa Shi Hosp Med Coll J 2013; 12(2): 19-22